Modal parameters and fault transients in double-circuit transmission lines : on the effects of conductor transposition, shield wires, and lossy soil modeling - Moraes, Caio Missiaggia (2023)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2023.